2019
DOI: 10.1371/journal.pone.0214945
|View full text |Cite|
|
Sign up to set email alerts
|

The magnitude of sex differences in verbal episodic memory increases with social progress: Data from 54 countries across 40 years

Abstract: Sex differences in episodic memory have been reported. We investigate (1) the existence of sex differences in verbal and other episodic memory tasks in 54 countries, and (2) the association between the time- and country-specific social progress indicators (a) female to male ratio in education and labor force participation, (b) population education and employment, and (c) GDP per capita, and magnitude of sex differences in verbal episodic memory tasks. Data were retrieved from 612 studies, published 1973–2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Although less is known about the physiological processes that render episodic memory vulnerable in PD, there are reasons to suspect that biological sex and/or sex hormones play important roles. First, episodic memory is characterized by lifelong sex differences in healthy humans (46)(47)(48)(49). Further, sex differences also mark the incidence and severity of episodic memory deficits seen during cognitive aging (47,50,51) in schizophrenia (52,53) and in Alzheimer's disease (54)(55)(56)(57).…”
Section: Introductionmentioning
confidence: 99%
“…Although less is known about the physiological processes that render episodic memory vulnerable in PD, there are reasons to suspect that biological sex and/or sex hormones play important roles. First, episodic memory is characterized by lifelong sex differences in healthy humans (46)(47)(48)(49). Further, sex differences also mark the incidence and severity of episodic memory deficits seen during cognitive aging (47,50,51) in schizophrenia (52,53) and in Alzheimer's disease (54)(55)(56)(57).…”
Section: Introductionmentioning
confidence: 99%
“…Results from this meta-analysis also indicated that the magnitude of these differences had remained stable since 1973 and that, for verbal tasks, the sex difference was somewhat smaller in childhood and old age than for other ages. Although the underlying mechanism for these sex differences are poorly understood, they have been reported in most of the examined countries (Bonsang et al, 2017;Asperholm et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy aging, men demonstrate faster rates of cognitive decline in key cognitive domains than women (McCarrey et al, 2016). For example, older women tend to perform better than older men on episodic memory (a domain affected in early stages of AD; Asperholm et al, 2019;Herlitz and Rehnman, 2008;, and have lower age-related declines in brain volume than men (Jack et al, 2015;Pfefferbaum et al, 2013). Again, these suggest that some women have greater resistance to AD than men.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to incorporate such characteristic differences in generations, including changes in economic, political, environmental, and social landscapes that may impact our understanding of sex differences in cognitive reserve. For example, measuring social progress indicators and/or living conditions may be relevant to incorporate in analyses of sex differences in cognitive reserve (Asperholm et al, 2019).…”
Section: Discussionmentioning
confidence: 99%